2013
DOI: 10.1021/nn405811p
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Colloidal InP Nanocrystals: Small Inorganic Ligands Boost High-Temperature Photoluminescence

Abstract: We examine the stability of excitons in quantum-confined InP nanocrystals as a function of temperature elevation up to 800 K. Through the use of static and time-resolved spectroscopy, we find that small inorganic capping ligands substantially improve the temperature dependent photoluminescence quantum yield relative to native organic ligands and perform similarly to a wide band gap inorganic shell. For this composition, we identify the primary exciton loss mechanism as electron trapping through a combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 38 publications
(61 reference statements)
6
70
0
Order By: Relevance
“…In the study of Wang et al, the authors observed significantly improved stability with the additional silica‐coated core/shell NCs. When they performed temperature stability test with the pristine core/shell NCs, their core/shell NCs can retain only 61% of their initial emission at 473 K and almost quenched emission at 573 K . Regarding the InP based QDs, in their work the authors studied the thermal stability of InP/ZnS up to 800 K and the results demonstrated that integrated PL of these NCs decreased to almost 10% of their initial value at around 500 K .…”
Section: Resultsmentioning
confidence: 64%
“…In the study of Wang et al, the authors observed significantly improved stability with the additional silica‐coated core/shell NCs. When they performed temperature stability test with the pristine core/shell NCs, their core/shell NCs can retain only 61% of their initial emission at 473 K and almost quenched emission at 573 K . Regarding the InP based QDs, in their work the authors studied the thermal stability of InP/ZnS up to 800 K and the results demonstrated that integrated PL of these NCs decreased to almost 10% of their initial value at around 500 K .…”
Section: Resultsmentioning
confidence: 64%
“…1 We found that the oleic acid capped CdSe/CdS NCs that were also made by high-temperature seeded growth 28 performed similarly to phosphonatecapped NR heterostructures ( Figure S4), indicating that at least among organic ligands the PL behavior is not affected by the ligand on the particles. However, we did not test an inorganic ligand, and we did not heat the samples above 600 K, situations in which it is possible that conclusions could be different.…”
Section: Articlementioning
confidence: 81%
“…208 In this regard, the PL temperature-dependence of InP/ZnS QDs has been investigated, [209][210][211] where the improved performance of the coreshell system over core-only InP was attributed to reduced electron trapping on the surface. 210 In addition to core-shell heterostructures, replacing long organic ligands on core-only InP with short inorganic ligands (S 2À as well as Sn 2 S 6 4À ), resulted in similar thermal stability, including PL recovery in cycling between 300 and 800 K. 210 …”
Section: Phosphors For Lightingmentioning
confidence: 99%